THE RELATIONSHIP BETWEEN EMOTIONS AND LANGUAGE COMPREHENSION - Malau, Sara Stefani; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
This research investigates the link between emotional states and language comprehension. It looks at how emotions can affect the cognitive processes involved in interpreting both spoken and written language, emphasizing how emotional experiences might either facilitate or obstruct understanding. Both positive and negative emotions are found to interact with key cognitive functions such as attention, memory, and reasoning, all of which play a crucial role in processing language. The findings suggest that the emotional context in which language is encountered can influence how individuals perceive and interpret information, thereby affecting both the ease and precision of language comprehension. Ultimately, the study aims to offer valuable insights into how emotions shape communication, learning, and cognitive functions in everyday language use.